North-south asymmetry in global distribution of the solar wind speed during 1985–2013 - Tokumaru, Munetoshi; 65720; Fujiki, Ken'ichi; 65721; Iju, Tomoya; 65722 (Journal of Geophysical Research: Space Physics, 2015)
Interplanetary scintillation (IPS) observations made between 1985 and 2013 are used to investigate the north-south (N-S) asymmetry in global distribution of the solar wind speed. The IPS observations clearly demonstrate that the global distribution of the solar wind speed systematically changes with the solar activity. This change is found to closely correlate with that in polar magnetic fields of the Sun, while fast wind data at solar minima systematically deviate from this correlation. The IPS observations show that notable N-S asymmetry of polar solar winds occurs at the solar maxima, and small but significant N-S asymmetry exists at the solar minima. The observed asymmetry at the solar maxima is consistent with the time lag in the reversal of polar magnetic fields between north and south hemispheres. We also find that significant N-S asymmetry of the polar fast wind lasts for the period between Cycles 23 and 24 solar maxima, starting from predominance of the fast wind over the north pole and ending with that over the south pole. The N-S asymmetry revealed from IPS observations is found to be generally consistent with Ulysses observations. We compare IPS observations with magnetic field data of the Sun and find that the ratio of the quadrupole to dipole coefficients exhibits a similar time variation to that of the N-S asymmetry revealed from IPS observations. This suggests that higher-order multipole moments play an important role in determining the N-S asymmetry of the solar wind when the dipole moment weakens. journal article